Potensi Dan Strategi Pengembangan Desa Wisata Kemetul Kecamatan Susukan Kabupaten Semarang - Aziz Widodo; Kasanah Kasanah; Siti Nurindah Sari (Indonesian Journal of Geography Education, 2021)
The potential and development strategy for the Kemetul Village tourism, Susukan sub-district, Semarang Regency 2020-2021. A Thesis. Geography Education. Faculty of Teacher Training and Education. Ivel University. 50 pages. The Republic of Indonesia is a country rich in natural beauty, flora and fauna as well as diverse cultures, all of which can provide substantial foreign exchange for the world of tourism. In general, tourism is seen as a sector that can encourage and enhance development, open new business fields, open employment opportunities and can increase people's income and local revenue in Kemetul Tourism Village. The objective of this study were (1) To determine the potential (2) development strategy of the Kemetul Village tourism, Susukan District, Semarang Regency. This research uses descriptive qualitative data type. Respondents who were sampled in this study were 3 people by interviews. The objectives of this study were (1) to determine the potential and development strategies of the Kemetul Tourism Village, Susukan District, Semarang Regency. This study uses qualitative descriptive data types. Respondents who were used as samples in this study were 10 people by means of interviews. The results of this research are (1) the Kemetul Village Tourism Area makes a gazebo and shooting star site which is intended to attract visitors to visit Kemetul Village. (2) In July Kemetul Village holds a tradition in the form of Julenan (alms of the earth) which invites the interest of visitors both from within the village and from outside the village, it is hoped that this tradition will make the existing harvest a blessing and for the next harvest to be more abundant again. (3) With the development of the Kemetul Tourism Village, it makes a growth point for the Susukan District and its surroundings because of tourism activities which have an impact on increasing economic activity and community income.